Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan pada PT XXX - Faiz Malida; Ety Nurhayati (Pusat Riset dan Inovasi Nasional, 2024)
In-depth research on the influence of leadership styles and work motivation on employee performance is essential for understanding how these factors interact and can be optimized. In an organizational context, this understanding can assist leaders and management in improving employee performance and achieving established business objectives. This study aims to identify and analyze the relationships between variables, specifically those affecting employee performance, leadership styles, and work motivation. Data collection was conducted using a non-probability sampling method, involving 50 respondents. Data was gathered through questionnaires and analyzed using multiple linear regression analysis with SPSS software. This research is quantitative in nature. The results indicate that leadership style has a significant impact on employee performance, while work motivation does not show a significant effect. Simultaneously, the variables of leadership style and work motivation significantly influence employee performance, as indicated by an Adjusted R Square value of 45.4%, which suggests that these variables together can explain 45.4% of employee performance, with the remainder explained by other factors.